Despondent officer narratives and the ‘post-Ferguson’ effect: exploring law enforcement perspectives and strategies in a southern American state - Deuchar, Ross (Policing and society, 2019)
The fatal shooting of a young, black, and male citizen named Michael Brown by a white male police officer in Ferguson (MO) generated political and media backlash that continues to erode law enforcement legitimacy today. Law enforcement is sensitive to changes in the public discourse on their profession and has responded in kind. A plethora of discussion has focused on the potential existence of a so-called ‘Ferguson Effect’, whereby de-policing has emerged among officers as a result of concerns about being subjected to negative media scrutiny for racial profiling or excessive use of force, in turn increasing crime rates. Unfortunately, the ‘Ferguson Effect’ is long on anecdotes but short on data. To better understand officers’ attitudes, perspectives, and strategies and the way in which the negative press related to the Ferguson incident interacted with these, in-depth semi-structured interviews with 20 law enforcement officials were supplemented with participant observations of officer deployments in two southern State counties in the United States. Officer confidence, morale, and policing strategies were queried within the post-Ferguson era. The data suggest that there had been an increased conceptual awareness of procedural justice but also a reduction in officer morale and emphasis on proactive policing strategies, and that Ferguson was often drawn upon as a reference point among officers. The implications for these findings are discussed in terms of future police policies and practices within a procedural justice framework that seeks to reduce crime and increase law enforcement legitimacy.